Air Quality Assessment In Wastewater Treatment Plant And Its Respiratory Effects On Workers In Al-Diwaniyah City - Mizher, MSc, Zahraa Riyadh; Ali, Ph. D, Luma Hussein; Mohammed, Ph.D, Israa Jassem (Adolescência e Saúde, 2026)
Wastewater treatment plants are essential for environmental protection, however, they can generate airborne pollutants that pose potential health risks to workers, particularly affecting the respiratory system. The study aimed to assess air quality in Al-Diwaniyah wastewater treatment plant and evaluate its respiratory effects on workers. Aim: A cross-sectional analytical study was conducted among 108 workers in the wastewater treatment plant and sewer networks. Air pollutants were measured using the Horiba PG-350 device. Respiratory symptoms were assessed using a structured questionnaire, and lung function was evaluated using spirometry. Results: All measured air pollutants (H₂S, CO₂, SO₂, NOx, CH₄, and CO) were significantly higher in the plant compared to the control area (P < 0.01). Respiratory symptoms were common, particularly breathlessness (52.8%), dry cough (49.1%), and chest tightness (40.7%). Spirometry results indicated reduced lung function, with mean FEV1 (1.87 ± 0.72) and FEV1/FVC ratio (58.16 ± 16.25). ), suggesting an obstructive pattern. Conclusion: Occupational exposure in the wastewater treatment plant is associated with elevated levels of air pollutants, increased prevalence of work-related respiratory symptoms, and impaired lung function among workers.